Bioinspired synthetic peptide-based biomaterials regenerate bone through biomimicking of extracellular matrix - Sareh Azadi; Mohammad Ali Yazdanpanah; Ali Afshari; Niloofar Alahdad; Solmaz Chegeni; Abdolhamid Angaji; Seyed Mahdi Rezayat; Shima Tavakol (Journal of Tissue Engineering)
There have been remarkable advancements in regenerative medicine for bone regeneration, tackling the worldwide health concern of tissue loss. Tissue engineering uses the body’s natural capabilities and applies biomaterials and bioactive molecules to replace damaged or lost tissues and restore their functionality. While synthetic ceramics have overcome some challenges associated with allografts and xenografts, they still need essential growth factors and biomolecules. Combining ceramics and bioactive molecules, such as peptides derived from biological motifs of vital proteins, is the most effective approach to achieve optimal bone regeneration. These bioactive peptides induce various cellular processes and modify scaffold properties by mimicking the function of natural osteogenic, angiogenic and antibacterial biomolecules. The present review aims to consolidate the latest and most pertinent information on the advancements in bioactive peptides, including angiogenic, osteogenic, antimicrobial, and self-assembling peptide nanofibers for bone tissue regeneration, elucidating their biological effects and potential clinical implications.